County-level environmental carrying capacity and spatial suitability of coastal resources: A case study of Zhuanghe, China - Yin, Shusheng; Guo, Jianke; Han, Zenglin (Frontiers in Marine Science, 2022)
The coastal zone is a combination of marine and land ecosystems, which represents the core areas of resource utilization in China. The sustainable development of coastal zones should be based on a deep understanding of their resources. Compared with Europe and North America, knowledge of coastal zone resources is more fragmented in China. In recent years, China has used quantitative models to realize integrated coastal zone management, but the theoretical basis and research methods remained incomplete. To this end, we developed an assessment framework for coastal zone territorial space resources, environmental carrying capacity, and spatial suitability from an integrated coastal zone management perspective. We tested this framework in Zhuanghe City, which is located within the Northeast Asian Economic Circle. The results show that the coastal resources and environmental carrying capacity of Zhuanghe City are mainly in a critical state. Land space in the coastal zone is mainly suitable for development, but the functional suitability of different regions significantly differs as more suitable urban areas are clustered on the coastal plain. The proportion of suitable space for agricultural production is ~50.51% and is mostly concentrated on the eastern coastal plain. The proportion of space with high ecological suitability is 14.17%, but it is concentrated in the northern mountainous area; there is low space for high value fishery production. Evaluation of coastline function shows that coastline suitable for production occupies a relatively high proportion, with a length of ~230.63 km, accounting for 80.92% of the total length of the Zhuanghe coastline. The ecological coastline of Zhuanghe City is occupied by industrial development and urban construction; suitable and unsuitable areas overlap and coastline development functions conflict with each other. Therefore, the coastal zone of Zhuanghe City is under great pressure. In China, coastal cities are the final link of integrated coastal zone management. Our research reveals a previously unreported critical situation in the coastal area of Zhuanghe City, especially in terms of fishery and shoreline utilization, which is worrisome in view of the reported production capacity of the city. Our results offer a reference for improving coastal management practices with the aim of alleviating the conflict between spatial development and protection in coastal areas.